Exploring the Impact of Learning Styles on Speaking Anxiety: A Qualitative Study of English Education Students in Indonesia - Restu Anugrawan; Ita Sarmita Samad; Musdalifah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study aims to investigate the relationship between learning styles and speaking anxiety among first-semester English Education Department students at Muhammadiyah University of Enrekang. Speaking anxiety is a significant barrier to language learning, often exacerbated by mismatches between students' learning styles—visual, auditory, or kinesthetic—and traditional teaching methods. To explore this relationship, a qualitative research approach was employed, with data collected through semi-structured interviews and document analysis involving 18 participants. The semi-structured interviews were designed to gather students' perspectives on their learning preferences, experiences with speaking anxiety, and how these factors influenced their speaking performance. The document analysis included an examination of academic records, feedback from instructors, and reflective journals, which provided additional insights into students' speaking challenges and coping mechanisms. The findings reveal that students' learning styles significantly influence their experiences of speaking anxiety. Visual learners struggle with spontaneous speaking tasks due to their preference for preparation and reliance on visual aids. Auditory learners face challenges with pronunciation, often fearing their spoken English will not sound